2017
DOI: 10.1021/acsami.7b14448
|View full text |Cite
|
Sign up to set email alerts
|

Photoresponsive and Magnetoresponsive Graphene Oxide Microcapsules Fabricated by Droplet Microfluidics

Abstract: Fluid compartmentalization by microencapsulation is important in scenarios where protection or controlled release of encapsulated species, or isolation of chemical transformations is the central concern. Realizing responsive encapsulation systems by incorporating functional nanomaterials is of particular interest. We report here on the development of graphene oxide microcapsules enabled by a single-step microfluidic process. Interfacial reaction of epoxide-bearing graphene oxide sheets and an amine-functionali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…In recent years, the Pickering emulsion method, which uses solid particles instead of traditional surfactants as emulsifiers and stabilizes the emulsion, has gradually become an effective and economical strategy for preparing microcapsules. [27][28][29] Graphene oxide (GO), as the precursor of graphene, [30][31][32] has a typical amphiphilic structure. 33 The study on the wettability of GO found that its contact angle is 62 to 68 , which makes GO particles more resident in water rather than oil, and tends to be stable in O/W emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the Pickering emulsion method, which uses solid particles instead of traditional surfactants as emulsifiers and stabilizes the emulsion, has gradually become an effective and economical strategy for preparing microcapsules. [27][28][29] Graphene oxide (GO), as the precursor of graphene, [30][31][32] has a typical amphiphilic structure. 33 The study on the wettability of GO found that its contact angle is 62 to 68 , which makes GO particles more resident in water rather than oil, and tends to be stable in O/W emulsion.…”
Section: Introductionmentioning
confidence: 99%
“…et al reported on the development of GO microcapsules enabled by a single‐step microfluidic process. The dual magnetic and photoresponsive characteristics, combined with the use of a single‐step process employing biocompatible fluids, represented highly compelling aspects for practical applications . Shang et al fabricated GO fibers with a spindle‐knotted structure and photothermally responsive phase‐transition behaviours by combining spinning and emulsification procedures in microfluidics.…”
Section: Application Of Graphene‐based Microfluidicsmentioning
confidence: 99%
“…Z. X. Luo et al reported that well‐designed microcapsules were fabricated using a droplet‐based microfluidic technique for controlled drug release. G. Kaufman et al fabricated photoresponsive and magnetoresponsive graphene oxide microcapsules by droplet microfluidics. D.V.…”
Section: Introductionmentioning
confidence: 99%
“…Kaufman et al 33 In this work, an ultraviolet-curable (UV-curable) polysiloxane was synthesized. Then flame-retardant microcapsules with a DMMP cores and a UV-curable polysiloxane shells were fabricated by the approach of microfluidic.…”
mentioning
confidence: 99%